Study of phosphor Ba2Si3O8:Eu2+ to produce WLED devices with support from ZnCdSe/ZnSe quantum dot - Huu Phuc Dang; Bui Van Hien; Nguyen Le Thai (Institute of Advanced Engineering and Science, 2022)
We created the blue-green Ba2Si3O8:Eu2+ (or BaE) phosphor treated with Eu2+ using the standard solid-state method with the concentration of Eu as well as heating temperature properly adjusted for the maximum luminescence efficacy. It is possible to excite the said phosphor using near-UV (n-UV) wavelengths and to display its wide emission band, which is the 5d => 4f shift for Eu2+, caused by the combination of the Eu activator and the nearby host. We integrated the said phosphor with the n-UV LED to create the pc-LED (short for diodes based on conversion phosphor). For the task of creating the WLED device that yields significant color rendering index, we combined the orange ZnCdSe/ZnSe quantum dot with a distinctive sheet structure for the pc-LED made with phosphor BaE. This research demonstrates the electroluminescence features of the said elements.